The Challenges of ASEAN Economic Community (AEC) in Sharia-Based Small and Medium Enterprises (SMEs) from The Social Capital Aspects - Nurlasera Nurlasera; Qomariah Lahamid (Lembaga penelitian dan pengabdian kepada Masyarakat, 2021)
This study evaluated the attributes of social capital that influence the business performance of sharia-based SMEs in Pekanbaru. This research is expected to provide contributions and inputs for SMEs in facing the challenges they enconter in the era of AEC and for the government in making the policy. The methode used is a quantitative descriptive and an inferential analysis. The population of this study is all players in the Sharia-Based SMEs in Pekanbaru that is unknown numbers. In this research, there are 70 respondents. The results showed that the partial reciprocity significantly affected the performance of sharia-based SMEs; while norms, networks, values and proactive action also gave positive effects, but they were not significant. Simultaneously, the six attributes of social capital influenced on the performance of the SMEs significantly. The coefficient of determination is 0.664. It means that the variable of norms, trust, networking, reciprocity, value, and strong desire jointly determine the performance variable of 66.4%. Most of sharia-based SMEs are optimistic to resume the business in the era of ACE (Asean Community of Economi).